Smart Story Archive for WhatsApp Status: A Design Thinking-Based Model for Private Status Retrieval - Nadya Lathifah Riady; Wahyu Kusuma Putra; Rizky Kwarta Ardhana (Forum Kerjasama Pendidikan Tinggi (FKPT), 2026)
WhatsApp Status supports quick sharing of daily moments, yet its 24-hour visibility creates a gap between temporary public sharing and private long-term retrieval. Existing story features mainly emphasize posting and viewing, while private retrieval by date, person, location, keyword, media type, favorite mark, and download access remains limited in WhatsApp Status. This study proposes Smart Story Archive as a user-centered design concept for private Status retrieval. The method used Design Thinking with survey-based needs analysis involving 100 experienced WhatsApp users, selected because they actively used WhatsApp Status and could evaluate archive-related pain points. This study contributes a theoretical and empirical framework for ephemeral data retrieval in private messaging environments by introducing a conceptual model that reconciles user desires for both ephemerality and long-term memory accessibility. The data were analyzed using descriptive statistics and translated into feature requirements and a high-fidelity prototype in Google Stitch. The key findings show three dominant needs: users want to recover meaningful Status memories, retrieve content through incomplete memory cues, and maintain privacy control over archived metadata. The proposed design addresses these needs through multi-cue search, optional private archiving, metadata control, and deletion access. This study contributes a WhatsApp-specific archive model that balances memory retrieval, privacy, and interface simplicity for future usability testing.